Implementation of Medical Rehabilitation and Social Rehabilitation for Addicts and Victims of Drug Abuse - Susi Delmiati; Irsal (Ekasakti Journal of Law and Justice, 2023)
The implementation of medical rehabilitation and social rehabilitation for addicts and victims of drug abuse by the National Narcotics Agency of Payakumbuh City is for drug addicts who are undergoing judicial proceedings can be placed in medical rehabilitation institutions and / or social rehabilitation. For addicts, both those caught and those through the IPWL program, before rehabilitation is carried out, they will first go through an assessment carried out by an integrated assessment team.  In addition to medical treatment and/or rehabilitation, healing of drug addicts can be organized by government agencies or the community through religious and traditional approaches. The obstacle faced by the Payakumbuh City National Narcotics Agency in the implementation of medical rehabilitation and social rehabilitation of addicts and victims of drug abuse is that the recommendation letter of the integrated assessment team consisting of the medical team and the legal team is only a recommendation. Rehabilitation places in each area have not been fulfilled (none). Weak coordination between law enforcement, health services and social services. Optimization of the implementation of medical rehabilitation and social rehabilitation for addicts and victims of drug abuse at the National Narcotics Agency Payakumbuh City is carried out with counseling, supervision and monitoring, carried out so that victims of narcotics abuse do not return to using narcotics under any conditions by checking periodically for 4 months after completing rehabilitation at BNNK Payakumbuh. Optimization is measured from the results of the rehabilitation and the number of people who participate in rehabilitationRehabilitation participants then no one repeats. This shows that the implementation of rehabilitation has been optimal.